Samorząd terytorialny wobec sektora MŚP - ze szczególnym uwzględnieniem pomocy publicznej - Markowska-Przybyła, Urszula (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper presents the special role of small and medium-sized enterprises sector (SME sector) in regional economy as well as local government's tasks (as entity particularly interested and responsible for supporting this sector) - taking especially public aid into consideration.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 11-20